An endogenous approach to the cyclicality of R&D investment under credit constraints: Firms' cash flow matters! - Juan Laborda; Vicente Salas-Fumás; Cristina Suárez (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This paper examines the sensitivity of firms' R&D expenditures to being externally financial constrained to undertake innovation projects, considering that being constrained is endogenous. It focuses on devising a model that enable us to explore the combined impact of liquidity constraints, demand shocks, and credit cycle on the cyclically of R&D, controlling by the firms characteristics. The methodology proposed consists of jointly estimating three interrelated equations with mixed distributions of dependent variables. The results obtained complete and improve those of the previous research. It is found that the effect of the business cycle on the perception of external financial constraints is subject to the availability of internal funds in each firm. On the other hand, constrained firms expend in R&D halve of the unconstrained ones, and the sensitivity of firms' R&D expending to GDP is countercyclical in firms with low cash flows and procyclical in firms with high cash flows. The R&D expending of firms is negatively associated with the aggregate leverage ratio of the non-financial sector. These results mean that business decisions, in particular R&D expending decisions, and macroeconomic variables are strongly related. A better understanding of these interrelations should help in designing macroeconomic policies aimed at stabilizing the economy and reduce growth volatility.
Keywords: 650; business cycle; credit cycle; financial constraints; R&D expending